Micro e pequenas empresas: um estudo sobre sua mortalidade prematura - Silva, Ricardo Luiz da (2002)
This paper propose a series of administraUve steps to avoid the premature death of the MPEs. These instructions were made starting from data collected (on a study case) within twelve MPEs businessmen, in-family or not, in boroughs of Baixada Fluminense, in the State .of Rio de Janeiro, who were able to be wefl succeeded in their business and were able to surpass crisis. The results of this survey indicate that: the main difficulties and distress factors faced by the MPEs during their first years of operation, and which are related to the extinction process, are the high taxes and tributes and the lack of capital good commitments; the entrepreneurs capable to survive the crisis within their business had administrative capabilities, persuasive communication on trade and also interpersonal, among other things; there is not any large influence regarding the regional area for the success or failure of the MPEs; the academic graduation of the entrepreneurs may be a determinant factor for the MPEs success, the adoption of administrative tools and the search for institutions, like SEBRAE, class associations, etc., to obtain support on the implementation and management, which would avoid the premature failure during their initial years of creation. There are several relevant factors for the MPE& success, among which a good market s knowledge where the business will be acting, a good management, the search for fiscal and legal support, and finally, the businessman profile, a fundamental tool for the MPE success.